Adolescents suppress emotional expression more with peers compared to parents and less when they feel close to others. (January 2023) - Wylie, Megan S.; De France, Kalee; Hollenstein, Tom
Adolescence is characterized by frequent emotional challenges, intense emotions, and higher levels of expressive suppression use than found in older populations. While evidence suggests that contingent expressive suppression use based on context is the most functional, it remains unclear whether adolescents use expressive suppression differentially based on social context. Because the peer relationship is highly salient in adolescence, the current study was designed to assess whether adolescents use expressive suppression differentially based on their social context. Adolescents ( N  = 179, Mage  = 13.94, 49.2% female) reported emotional events using experience sampling via a smartphone application for 14 days. Multilevel modeling revealed that adolescents used less expressive suppression when they were alone compared with when they were with people, and used more expressive suppression when they were with their peers compared with when they were with family. In addition, more closeness with family predicted less overall expressive suppression use, while closeness with peers did not influence the level of expressive suppression use within the peer context. We discuss the importance of peer relations in adolescence and the relationship between closeness and emotional expression.